THE RISE OF CHILDREN DROPPING OUT OF SCHOOL IN RAJA AMPAT - Muhamad Yusuf Yusuf; Andi Bugis; Suparto Iribaram; Dyan Pratiwi (STAI Hubbulwathan Duri, 2020)
This study aims to determine the factors that cause the high number of children dropping out of school in Yellu Village, South Misool District, Raja Ampat Islands. This is a qualitative research with a social phenomelogy paradigm and was conducted in Yellu Village, South Misool District, Raja Ampat Islands. The number of children dropping out in Yellu Vilage was influenced by two factors. Internal factor includes lack of motivation from them in order to improve education. Some of external factors are lack of parental supporting, associating with their peers who are not in school, children who easily earn some money without going to school due to the emergence of pearl companies that requires labor and abundant marine resources to get fish and seaweed, unsupportive educational facilities, lack of supporting from local government and the private sector in order to education development.